"Щасливе пророцтво", або "Прогностик щасливий": панегірик Пилипа Орлика миргородському полковникові Данилу Апостолу - Пришляк, В.; Ґжеськов’як, Р.; Циганок, О. (Сiверянський лiтопис, 2019)
The article presents the foreword and the first publication of the original panegyric text in Polish language. The first translation into Ukrainian language with notes and comments to the unknown panegyric written by Pylyp Orlyk at 1690's were completed. The panegyric was dedicated to the glorification of the Myrhorod colonel Danylo Apostol’s victory over the Crimean Tatar army in 1692, when the Myrhorod Regiment of the Hetmanate repelled a large yasir and returned to the looted property. In the elegant allegorical form, the panegyric predicted the inevitability of the Cossack victory in the following year of 1693 thanks to God's patronage, the coat of arms and the military talent of an experienced Colonel. In poetic panegyric form, Pylyp Orlyk not only paid tribute to the coat of arms’ tradition, but also synthesized the symbols of various eras within the aesthetics of Baroque culture. The comparison of this poem with his other works, as well as polonomic poetry by Lazar Baranovych and Ivan Ornovsky, allows us to place accents and try to depict a wider background of Baroque battle poetry. Historical reconstruction of the context of the preceding events that took place during and after this military campaign allows us to conclude that the heroization and even sacralization of the specific historical figures of the Cossack Hetmanate took place in the panegyric works usual for this period that implemented the style of Greek antique mythology. The single original of the poem with the imprint of Ivan Shchyrsky is currently kept in the Krasinsky collection in Old Prints department of the National Library of Poland in Warsaw. The literary analysis of the text, which is hard to read in some parts, makes it possible to substantially expand and supplement the data to the prosopographical portrait of the Cossack Staff officers (starshyna) and the intellectual creative elite of the Hetmanate. It helps to trace the characteristic features of the development of an allegorical poetic image in Ukrainian heroic poetry and engraving of the Mazepa Baroque times.